Effect of antenatal class attendance on fear of childbirth and antenatal stress - Yörük, Selda; Acikgoz, Ayla (Revista de Saúde Pública, 2023)
OBJECTIVE: To assess the effect of attending antenatal classes on fear of childbirth and antenatal stress in nulliparous pregnant women. METHODS: A total of 133 nulliparous pregnant women participated in the study, which had a quasi-experimental design. Data were collected by a descriptive data form, the Wijma Delivery Expectancy/Experience Questionnaire, and the Antenatal Perceived Stress Inventory (APSI). RESULTS: A significant correlation was found between antenatal class attendance and having a high schooling level and an intended pregnancy (p < 0.05). The mean fear of childbirthscore of pregnant women was 85.50 ± 19.41 before the training and 76.32 ± 20.52 after the training, and the difference between these scores was significant (p < 0.01). Fear of childbirth scores were not significantly different between the intervention group and the control group. The mean APSI score of pregnant women in the intervention group was 22.32 ± 6.12 before the training and 21.79 ± 5.97 after the training. However, this difference was not statistically significant (p = 0.70). CONCLUSION: The fear of childbirth score decreased significantly in the intervention group after the training.